Acceptability and Nutritional Evaluation of Moringa Mung Bean Velva as a Supplementary Snack for Stunted Children - Putri Aniq Oktavia; Dr. Ir. Juliana Christyaningsih, M.Kes.; Melina Sari STP, M.Si (Journal of Nutrition Explorations, 2025)
Stunting is a chronic nutritional disorder in toddlers, characterized by a height-for-age Z-score (HAZ) below the WHO standard due to prolonged inadequate nutrient intake. This study aimed to evaluate the acceptability and nutritional content of Moringa mung bean velva as an alternative functional snack for stunted children. A post-test only control group design was used to test three velva formulations with a fixed amount of moringa powder (15 g) and varying mung bean amounts (50 g, 60 g, and 40 g). A hedonic test involving 25 trained panelists was conducted and analyzed using Kruskal Wallis and if there is a difference continue with the Mann Whitney Test (p < 0.05), while protein and fiber levels were measured using the Kjeldahl and gravimetric methods. The KH03 formulation (40 g mung bean : 15 g moringa) received the highest overall acceptance (mean score: 3.33), particularly in color (3.68), texture (3.32), and taste (3.44), and contained 9.75% protein and 3.24% fiber per 100 g. These findings indicate the potential of velva KH03 as a local functional snack that is both nutritious and organoleptically acceptable for stunting prevention.